The parametres [sic] of postmodernism - Zurbrugg, Nicholas (Routledge, 1993)
This ground-breaking work draws upon the authors interviews with leading postmodern artists, including Baudrillard, Beckett, Cage and Glass. It offers a challenging and positive view of postmodern culture.